1896
DOI: 10.1098/rsta.1896.0003
|View full text |Cite
|
Sign up to set email alerts
|

III. Experiments on fluid viscosity

Abstract: These experiments consisted of the measurement of the moment transmitted, by fluid viscosity, across the annular space between two concentric cylinders, one of which revolves while the other is stationary. The fluid used in these experiments was water. Three distinct sets of conditions were tried, viz. :- (1) Outer cylinder revolving, inner cylinder stationary. (2) Inner cylinder revolving, outer cylinder stationary. (3) Repetition of series (1) with an annulus of different width.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1
2

Year Published

1921
1921
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(29 citation statements)
references
References 0 publications
3
23
1
2
Order By: Relevance
“…For a rotating outer cylinder with an inner cylinder at rest, Taylor concluded that the flow was always stable. These results were in contrast with the earlier experiments by Couette (1890) and Mallock (1896).…”
Section: Bagnold's Torque Measurements For Pure Watercontrasting
confidence: 56%
See 1 more Smart Citation
“…For a rotating outer cylinder with an inner cylinder at rest, Taylor concluded that the flow was always stable. These results were in contrast with the earlier experiments by Couette (1890) and Mallock (1896).…”
Section: Bagnold's Torque Measurements For Pure Watercontrasting
confidence: 56%
“…Prior to 1954, several studies examined single-phase flow between a rotating outer cylinder and stationary inner cylinder (Couette 1890;Mallock 1896;Wendt 1933;Taylor 1936a, b; see the review by Koschmieder 1993). Although Bagnold did not compare his pure fluid results with these studies, the experimental parameters are similar and a comparison demonstrates the impact of Bagnold's experimental apparatus on his stress measurements.…”
Section: Bagnold's Torque Measurements For Pure Watermentioning
confidence: 80%
“…It is also worth noting that plane Couette flow is the limiting case of TC when the radius ratio η = 1. Experimental investigations of TC have a long history, dating back to the initial work in the end of the 1800s by Couette (1890) in France, who concentrated on outer cylinder rotation and developed the viscometer and Mallock (1896) in the UK, who also rotated the inner cylinder and found indications of turbulence. Later work by Wendt (1933) and Taylor (1936), greatly expanded on the system, the former measuring torques and velocities for several radius and rotation ratios in the turbulent case, and the latter being the first to mathematically describe the cells which form if the flow is linearly unstable.…”
Section: Optimal Taylor-couette Flow: Radius Ratio Dependencementioning
confidence: 99%
“…The history of fluid dynamics in short cylindrical Couette systems extends to the 19th century [7], but our experiment is atypical in several respects. Since the pioneering work by Benjamin [8][9][10], the majority of such work has used a stationary outer cylinder with stationary caps, the main interest being the influence of the short geometry on TCI.…”
Section: Introductionmentioning
confidence: 99%